Postural stability in healthy child and youth athletes: The effect of age, sex, and concussion-related factors on performance - Paniccia, M.; Wilson, K. E.; Hunt, A.; Keightley, M.; Zabjek, K.; Taha, T.; Gagnon, I.; Reed, N. (Sports Health: A Multidisciplinary Approach, 2018)
Background: Postural stability plays a key role in sport performance, especially after concussion. Specific to healthy child and youth athletes, little is known about the influence development and sex may have on postural stability while considering other subjective clinical measures used in baseline/preinjury concussion assessment. This study aims to describe age- and sex-based trends in postural stability in uninjured child and youth athletes at baseline while accounting for concussion-related factors. Hypotheses: (1) Postural stability performance will improve with age, (2) females will display better postural stability compared to males, and (3) concussion-like symptoms will affect postural stability performance in healthy children and youth. Study Design: Cross-sectional study. Level of Evidence: Level 3. Methods: This study comprised 889 healthy/uninjured child and youth athletes (54% female, 46% male) between the ages of 9 and 18 years old. Participants completed preseason baseline testing, which included demographic information (age, sex, concussion history), self-report of concussion-like symptoms (Post-Concussion Symptom Inventory [PCSI]-Child and PCSI-Youth), and measures of postural stability (BioSway; Biodex Medical Systems). Two versions of the PCSI were used (PCSI-C, 9- to 12-year-olds; PCSI-Y, 13- to 18-year-olds). Postural stability was assessed via sway index under 4 sway conditions of increasing difficulty by removing visual and proprioceptive cues. Results: In children aged 9 to 12 years old, there were significant age- (P < 0.05) and sex-based effects (P < 0.05) on postural stability. Performance improved with age, and girls performed better than boys. For youth ages 13 to 18 years old, postural stability also improved with age (P < 0.05). In both child and youth subgroups, postural stability worsened with increasing concussion-like symptoms (P < 0.05). Conclusion: There are developmental and baseline symptom trends regarding postural stability performance. Clinical Relevance: These findings provide a preliminary foundation for postconcussion comparisons and highlight the need for a multimodal approach in assessing and understanding physical measures such as postural stability.